Wakenight Emporium - West, A. B. (Florida FC2, 2002)
Wakenight Emporium holds much for the philosopher, much for the poet, but there are also boundless riches here for the physicist, as West fascinates us with force, motion, velocity, and gravity. Her writing is the love-child of Einstein and Heidegger, obsessed with clicks of the second hand, the intricacies of now, the visible penetrations of genius. And in the midst of all, this book wants to blow the readers head open. What remains in the half-state between dreams and waking is a universe of stars.
Keywords: Fiction